Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3892/or.2012.2058
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 induces the overexpression of miR-222 and miR-221 and increases growth and motility in papillary thyroid cancer cells

Abstract: Experimental and epidemiological studies have revealed that chronic inflammation contributes to cancer progression and even predisposes to cellular transformation. Inflammatory infiltrates in papillary thyroid cancer include lymphocytes, macrophages and cytokines. High-mobility group box 1 protein (HMGB1) is a late inflammatory cytokine that signals danger to the immune system through the receptor for advanced glycation end-products (RAGE) and Toll-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 20 publications
3
49
0
Order By: Relevance
“…It has been reported that HMGB1 has a postive correlation with inflammatory responses and various cancer progression [23]. Meanwhile, HMGB1 is proved to be the target of miRNAs [25], such as miR-200c, or regulate some miRNA including miR-222 and miR-221 [26] to inhibit or promote the invision and metastasis of various tumor cells. In the present study, we explored the molecular mechanism of HMGB1 in nonsmall cell lung cancer cells and explored the role of HMGB1 in tumorigenesis and progression of lung cancers.…”
Section: Autophagy Is Detected In Ddp-resistant Cells A549/ddp or A54mentioning
confidence: 99%
“…It has been reported that HMGB1 has a postive correlation with inflammatory responses and various cancer progression [23]. Meanwhile, HMGB1 is proved to be the target of miRNAs [25], such as miR-200c, or regulate some miRNA including miR-222 and miR-221 [26] to inhibit or promote the invision and metastasis of various tumor cells. In the present study, we explored the molecular mechanism of HMGB1 in nonsmall cell lung cancer cells and explored the role of HMGB1 in tumorigenesis and progression of lung cancers.…”
Section: Autophagy Is Detected In Ddp-resistant Cells A549/ddp or A54mentioning
confidence: 99%
“…Higher expression levels of those miRs were detected in cancers presenting with capsular and vascular invasion or lymph node metastasis (51). OncomiRs miR-221 and miR-222 were reported to play a role in PTC aggressiveness (52) and, in the Cancer Genome Atlas (TCGA) data, were associated with less-differentiated tumors (47). In TCGA data, a more aggressive phenotype of thyroid cancer was also correlated with overexpression of miR-21 and miR-146b, as well as the loss of miR-204 (47).…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…Similarly, the present study reports that HMGB1 has an effect on neuroblastoma cell lines by enhancing miR-221 and -222 expression in both MYCN-amplified and non-amplified cell lines. The growth increase induced by HMGB1 in SK-N-BE(2) cells may be explained by the known association between N-Myc transcription factor and HMGB1, which acts on AKT-activating pathways (22). Furthermore, the present study showed that HMGB1 enhances miR-221/222 expression and induces growth in SK-N-BE(2) cells.…”
Section: Discussionmentioning
confidence: 49%